Pulmonary Large Cell Carcinoma Expressing Neuroendocrine Markers: The Morphological, Biological, and Neuroendocrine Features of Their Cell Lines and Surgical Cases - Kasai, Kiyoshi (Jpn J Cancer Res, 1992)
A cell line expressing neuroendocrine (NE) markers, designated as KTS9, was established from a human large cell carcinoma of the lung using serum‐free medium, ACL‐3. KTS9 cells showed morphological characteristics of large cell undifferentiated carcinoma (LGUC) and expressed some general NE markers including neuron‐specific enolase (NSE), protein gene product (PGP) 9.5, neural cell adhesion molecule (N‐CAM), synaptophysin and neurofilaments (NF) of 200 kd. Some cells of this cell line were positive to chromogranin‐A (CG‐A), but did not express Leu7 or aromatic L‐amino acid decarboxylase (AADC). Such a cell line derived from LCUC with NE properties has not previously been reported. The biological and NE properties of the KTS9 cell line were compared with those of 2 surgical cases of LCUC with NE markers and of the KTA7 cell line previously reported to derive from large cell carcinoma and to possess NE markers such as alpha‐hCG, PGP9.5 N‐CAM and AADC. Tumor cells of 2 large cell carcinomas expressed NSE, PGP9.5, N‐CAM and NF. The KTS9 and KTA7 cell lines and 2 large cell carcinomas were thus considered to be LCUCs with NE differentiation. Both lines had the morphological characteristics of LCUC, relatively short doubling time and discordant expression of NE markers, indicating them to be closely related to the variant type of small cell carcinoma cell lines and thus possibly to represent high‐grade malignancy. They may be useful for examining the biological behavior and NE features of large cell‐type NE tumors of the lung.